Ethnobotany of Medicinal Plant Diversity as A Traditional Medicine in Bugbug Karangasem, Bali, Indonesia - Dewa Ayu Sri Ratnani; I Ketut Junitha (PT FORMOSA CENDEKIA GLOBAL, 2025)
Traditions and cultures used as tourism assets can ignore traditional practices with a concurrent loss of traditional knowledge. This study aims to reveal the traditional knowledge of medicinal plants used by the Bugbug community through analysis of the traditional knowledge of the diversity of medicinal plants, the fidelity level (FL) and Index of Cultural Significance (ICS) of medicinal plants. The study was conducted in Bugbug Village, Karangasem, from May to July 2022. Data were collected using qualitative methods through semi-structured interviews, moderate participation observation, and documentation. Key informants and respondents were selected using purposive and snowball sampling; 10 informants and 48 respondents were obtained. The fidelity level was calculated by FL; and cultural importance by ICS. The level of traditional knowledge of medicinal plants was measured by the Phillips and Gentry equations and analyzed by the Kruskal Wallis and Mann Whitney Test. As many as 124 species in 46 families are found at Bugbug Village. The best represented families were Fabaceae. Leaves are the most widely used plant parts for traditional medicine. The highest habitat is obtained from the roadsides. In terms of the life form, most of the used species were herbaceous. Traditional knowledge between age groups differs significantly. In contrast, traditional knowledge of gender was not found to be different. The highest fidelity levels are Piper betle L. and Imperata cylindrica L. And the most ICS is Piper betle L